PANGSA PENGELUARAN PANGAN RUMAH TANGGA PETANI PADI-TERPADU DI KECAMATAN PANGKALAN KABUPATEN KARAWANG - Ugih Sugiarto; Tuti Karyani; Dini Rochdiani (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to identify the status of food security of paddy farmer households between monoculture and integrated farmers in Pangkalan District, Karawang Regency. The research was conducted from June to September 2018. This research is quantitative research with survey techniques. The sampling technique in this study was carried out by stratified random sampling . By identifying areas and farmers have potential in rice farming and cattle breeding then selected Tamanmekar village, Tamansari village, and Medalsari village in the Pangkalan district base has the highest number of integrated farming according to data from the initial survey prior to the study. The total number of samples obtained was 107 samples of monoculture farmers and integrated respondents. The number of samples is further divided into the number of respondents of monocultural rice farmers (61 respondents) and integrated farmers (46 respondents). Data analysis uses an analysis of the share of food expenditure and t test to determine the impact of integrated agriculture on household food security. Overall the number of farmer household respondents with the category of food expenditure share <60% or food resistance as many as 69 respondents (64.49%), while the number of households with a share of expenditure ≥ 60% or food insecurity was 38 respondents (35.51%) . The test results of different test using t test showed p-value obtained at 0, 344. When compared with the significant level of 5%, the p-value is greater so it is concluded that it is not there is a difference between the share of agricultural expenditure in the group of monoculture farmers and integrated farmers. It means that integrated farming doesn’t have an impact on food security.